LOW-MOLECULAR WEIGHT HEPARIN (LMWH) AS A PROPHYLAXISOF DEEP VEIN THROMBOSIS (DVT) IN TRAUMATIC PATIENTS - Megasafitri, Dian; **, Wiargitha; Maliawan, Sri (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Deep Vein Thrombosis (DVT) is the formation of a blood clot (thrombus) in a vein in which to channel blood back to the heart. Traumatic injury is one of the important risk factors for DVT formation. Thrombus formation involves three important factors include the blood flow, blood components, and blood vessels, known as Virchow's Triad. Classical findings of pain in the calf of foot at dorsiflexion position (Homans sign) is a sign of a specific but not sensitive and occurs in half of patients with DVT. A thorough history and physical examination is very important in the approach to patients with suspicion of having DVT. Radiological examination is an important examination in diagnosing DVT. Although there are many choices modality, the level 1 clinical evidence now supports the use of pharmacologic therapy with anticoagulants Low-Molecular Weight Heparin (LMWH) for primary DVT prophylaxis agent. Different types of LMWH have different indications approved by the Food and Drug Administration (FDA) as DVT prophylaxis based on the varieties of clinical evidence. Enoxaparin is the most widely indicated as a prophylaxis and treatment for DVT. Tinzaparin is indicated as a therapy, but not as a DVT prophylaxis in some groups of patients. Dalteparin is indicated as a prophylaxis, but not as a DVT therapy. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: DVT, LMWH, Enoxaparin